Philanthropy Movement for Economic Improvement in Pasuruan Regency During Covid-19 - Afandi, Achmad Syariel; Nadenta, Sekar Ayu; Ajizah, Sholikhatul; Khotimah, Siti Khusnul; Kamaliah, Aidah; Arsvendo, Dimas; Alivia, Dinda Namira; Rohman, Abid (Sultan Journal of Social Sciences and Humanities, 2024)
Indonesia confirmed the first case of infection with the corona virus that causes covid-19 in early March 2020. Since then, various countermeasures have been made by the government to reduce the impact of the Covid-19 pandemic in various sectors. Almost all sectors are affected, not only in the health sector. One of them is the economic sector which has also been seriously affected by the Covid-19 pandemic. Restrictions on community activities affect business activities which then have an impact on the economy. Weakening economic performance also has an impact on employment in Indonesia. Not a few companies choose to lay off and even lay off their workers. This has an impact on the declining economy of the community which makes it difficult for them to meet their daily needs. Therefore, a student group with seven members chose to help the community by partnering with the GEBRAKAN community which has the slogan "Take as much as you can, give as much as you can". Through a service learning approach, namely as a method of community service in the form of concrete actions obtained through classroom education and field practice. The method in implementing this community service program is grouped into three stages, namely 1) the pre-implementation stage, 2) the implementation stage, and 3) the post- implementation stage.